Perceptions of the fatigue experience and a breathing awareness meditation-integrated mHealth App for fatigue and stress in patients with sarcoidosis. Issue 1 (2nd January 2023) - Christon, Lillian M.; Chandler, Jessica; Benfield, Katie; Pairet, Samantha; Hoffman, Maria; Treiber, Frank; James, W. Ennis
ABSTRACT: Objective: Fatigue is a debilitating consequence of sarcoidosis, a multi-system inflammatory disease, potentially related to increased stress associated with the disease. Breathing awareness meditation has potential as an intervention for managing stress and fatigue for patients with sarcoidosis (PS). The project aim was to obtain feedback from key informants to design and tailor a patient-centered Sarcoidosis Patient Resource and Companion (SPARC) mHealth App developed for PS to manage fatigue/stress at home using meditation. Methods: A mixed-method patient/user-centered design was used with triangulation to understand patient experiences of sarcoidosis-associated fatigue and stress ( n =  13), and to obtain feedback on the SPARC App prototype integrating meditation from patients and health care team members (HCTMs; n  = 5). Using deductive content analysis, transcribed interviews were coded for themes/subthemes. Results: Themes indicated that sarcoidosis patients find fatigue to be a profoundly difficult and stressful experience affecting multiple domains of functioning with few effective strategies to cope with these challenges. Patients and HCTMs shared feedback on the SPARC App prototype after a test session and found it user friendly with potential to improve fatigue/stress. Key points for tailoring the App to patients were shared. Conclusion: Sarcoidosis-associated fatigue poses a significant burden for patients. The SPARC App prototype with breathing awareness meditation was acceptable, feasible and well-received by patients and HCTMs. Future iterations of the SPARC App to test the effect of meditation on fatigue will need to incorporate study recommendations for individual tailoring for these patients.